2010
DOI: 10.1007/s10641-010-9748-0
|View full text |Cite
|
Sign up to set email alerts
|

Bluehead chub nesting activity: a potential mechanism of population persistence in degraded stream habitats

Abstract: Aquatic biodiversity continues to decline as humans modify the landscape, mainly because of stream habitat alterations and loss caused by urban development. Bluehead chubs may mitigate some effects of instream habitat degradation by providing clean gravel substrate via their spawning nests. We used path analysis, an extension of multiple linear regression, to explore the relationships among instream habitat degradation, adult chub abundance, chub nesting activity, and chub reproductive performance. Age-0 chub … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
(43 reference statements)
1
33
0
Order By: Relevance
“…This method is effective because length‐frequency histograms of short‐lived temperate fishes such as cyprinids show distinct modal breaks. This method typically agrees well with age estimation based on hard structures (Reid, Jones & Yunker ; Peoples, Tainer & Frimpong ). The purpose of the binary age classification was not to quantify actual age structure, but to partition demography into indices of reproductive success (juvenile abundance) and a major cause of reproductive output (adult abundance).…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…This method is effective because length‐frequency histograms of short‐lived temperate fishes such as cyprinids show distinct modal breaks. This method typically agrees well with age estimation based on hard structures (Reid, Jones & Yunker ; Peoples, Tainer & Frimpong ). The purpose of the binary age classification was not to quantify actual age structure, but to partition demography into indices of reproductive success (juvenile abundance) and a major cause of reproductive output (adult abundance).…”
Section: Methodssupporting
confidence: 74%
“…the positive relationship between adult and juvenile abundance of a reproductive group). For example, models predicting nest abundance must contain large adult male abundance and gravel availability (Peoples, Tainer & Frimpong ). Because they reproduce almost exclusively on Nocomis nests, models predicting juvenile Nocomis and strong associate abundance must always contain nest abundance.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, 38 of 48 macroinvertebrate families recorded in the section of stream studied were found on chub nests, which is a significant concentration of macroinvertebrate families in the small area represented by nests in the stream. There is some preliminary evidence that chub nests may allow nestassociate fish species to persist in degraded streams, offering support to increasing consideration of Nocomis as keystone species (Vives 1990;Peoples et al 2011;Pendleton et al 2012). Dedicated research on interactions of stream macroinvertebrates with chub nests may find that chubs also facilitate the persistence of some members of macroinvertebrate communities.…”
Section: Resultsmentioning
confidence: 99%
“…We found the nests in pairs at each site, likely because multiple males put their nests in the most suitable conditions of flow and depth located at pool tails (Sabaj et al 2000;Bolton et al 2015). Our study did not examine stream flow, presence of riffles and pools, or other environmental conditions because these nest site conditions have already been studied in detail (Peoples et al 2011;Bolton et al 2015). We sampled the nests by first measuring the depth of the water at the nest location and two diameters of the nest.…”
Section: Methodsmentioning
confidence: 99%
“…Successful implementation of these methods depends critically on connecting the underrepresented taxa with the mechanisms responsible for their reduction/ elimination but often requires substantial scientific expertise. Although many previous studies have related human activities to resident species assemblages, few have confirmed or determined mechanisms (Peoples et al, 2011;Kemp, 2014). Common bioindicators often include benthic macroinvertebrates, fish, benthic diatoms, macrophytes and birds (Feld and Hering, 2007;Vaughn et al, 2007;Hughes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%